Проблемно орієнтовані системи та вибір моделей стратегій дій в умовах непередбачуваних загроз - Сабат, В. І.; Кугот, В. О. (ТОВ «Видавництво Ліра-К», 2025)
The article is focused on the development of models of operational management of complex hierarchically structured systems in conditions of threats associated with emergency situations, adhering to the strategies of a goal-oriented decision-making method in crisis conditions.
Keywords: стратегія дій; непередбачувана загроза